Measuring the Level of Fossil Energy Consumption, Economic Development, and International Trade on Co2 Emission Production in Indonesia - Wardani, Tri Ulfa; Herianto, Herianto; Haslindah, Haslindah (El-Barka, 2023)
Environmental health and climate change have become a global concern; there has been an increase in the amount of CO2 emissions from 1,720 million tons of CO2 equivalent in 2020 to 2,950 million tons of CO2 equivalents which has caused an increase in air temperature and widespread global warming. The purpose of this research is to see the relationship between energy consumption in the form of fossil energy, economic development, international trade and CO2 production in Indonesia. This research was built within the framework of a quantitative approach with an error correction model estimation model, data obtained from the world bank and world development indicators for the period from 1994-2021. Furthermore, the data is processed with the help of the STAT.17 application. Research to answer the question, do fossil energy consumption, economic development and international trade have short-term and long-term effects on the production of CO2 emissions in Indonesia. This study found that fossil energy consumption has both short and long term effects on CO2 emissions. Meanwhile, the variables of economic development and international trade only have a short-term effect. Thus this research is expected to be able to become the basis for strengthening to encourage the use of renewable energy towards sustainable development. This research is one of the comprehensive studies on economic development and environmental health.